الإشكالات العارضة لعلم أصول الفقه وأثرُها في تدريس بعض مباحثه في هذا العصر : (Occasional Problems Related to the Principles of Islamic Jurisprudence (Usull al-Fiqh) and its Impact on Teaching Some of its Topics in this Era) - (Mohamed Bashir Haj Salem), محمد البشير الحاج سالم (At-Tajdid - Intellectual Refereed Journal, 2021)
Abstract It is well known that Uṣūl Al-Fiqh is one of the sciences of Sharīʿah, that serves the science of jurisprudence Fiqh by regulating it methodologically, but some of the problems in Uṣūl Fiqh are reflected in Fiqh itself. Some of these problems have become intrinsic in Fiqh itself and this has affected the efforts of ijtihād until today. The problems are varied, some of them are methodological, others are terminological and substantive issues. This study would discuss only the substantive and methodological aspects that affect the topics in Fiqh, as being more impactful than others, to identify the most important regarding two aspects: traditional normalization and contemporary teaching. With a concise critical analytical approach, and based on a long educational experience, this study would investigate many topics of ʾUṣūl Fiqh, to reveal the most serious flaw that it caused, that are related to the chapter of “Shar’ī Judgment” (al-ḥukm al-shārʿī) and “Evidence of Rulings” (adillat al-aḥkām). Their relation to judgement: such as the confusion in the content in the topic on the permission and intention (al-rukhsah wa al-ʿazīmah). Another problem is the failure of the scholars to follow through the theoretical issues of some topics and concepts in the foundations of Fiqh: such as their failure to explain the importance of the Islamic rule of law in its epistemological sense, a flaw which has complicated distinguishing it from the practical reality of judgment among the jurists. Their neglect of the concept of exception to the rule in discussing the topics in Ūṣūl al-Fiqh. Other issues are related to evidence of judgments: such as exaggeration in the issuance of some comprehensive lawsuits, and a claim to limit the foundations of jurisprudence in the evidence of judgments, and a claim to deny certain meanings in certain terminologies. Some other problem that has not been solved for centuries had affected negatively legal education sector in this era. Subsequently, it had made the science of ʾUṣūl Fiqh to become more like a traditional science whose effect in directing and correcting the activity of contemporary jurisprudence is underrated and poor. Keywords: Problems, Uṣūl al-Fiqh, effect, teaching Uṣūl al-Fiqh.